(untitled) (Jurnal Bahasa, 2003)
This article reports the study on the errors in essays composed by Chinese secondary students in Sibu, Sarawak. The subjects are required to write essays. After the essays are corrected, certain language errors are found: morphlogy, syntax, paragraphing, mechanical, and textual connectors. It was also found that language errors are significantly related to the gender and the educational streaming, while the socioeconomics factors and residence are not related to the language errors.